The Church of England and social change in Manchester, 1635-1928. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
Manchester Cathedral is one of only a handful of Anglican cathedrals that hold their own archives on site. Dating from 1361 to the present day, its archives cover the parish functions of both the Cathedral and its predecessor, the Collegiate Church, founded in 1421, as well as of the capitular workings of the church. The collection contains the largest series of parish registers in the country, because of the peculiar coincidence of a very large parish with a huge population increase during the 18th and 19th centuries. At times of peak demand, more than a hundred couples would be wed in a single day, married in batches of 20-30. Yet not all would-be couples were married, as the Cathedral's apparently unique series of banns books starting from the Georgian period shows. These volumes provide unique insights for historians into the proportion of engagements that failed, what objections were raised, and by whom, as well as allowing detailed statistical analysis of residence and mobility in Victorian England. The Capitular Archives record the management of the Chapter Estates comprising considerable land holdings from the 17th-20th centuries in what became the world's first industrial city. Again it is possible to chart the effects of the Industrial Revolution on land use and property values in one of Britain's most important urban centres, as farms and fields were converted to roads, railways, homes and factories. Accessible through a full and detailed online catalogue of the entire fonds (Access to Archives), the materials chosen for publication include highlights from across the major collections. Each document selected serves to illustrate the parochial duties of the Chaplains and Churchwardens, including charity distribution and the daily management of the church and its fabric, as well as the land and financial management of the Warden and Fellows of the Collegiate Church. Taken altogether they reveal how the established church tried to cope not just with spiritual, but also with social and economic change on an unprecedented and massive scale. Accompanied by an online guide to the collection by Christopher Hunwick, formerly Manchester Cathedral Archivist.
Date range: 1635-1928.
Keywords: Church of England -- Registers; Social change -- England -- Manchester -- History; Manchester Cathedral (England) -- Registers; Christian sociology -- Church of England -- History